Comparative storage biology of tropical tree seeds - Sacandé, M.; Jøker, D.; Dulloo, Mohammad Ehsan; Thomsen, K.A. (2004)
Forest trees are an important element of the landscape and many have great economic and cultural value, providing and supporting the livelihoods of millions of people, especially in the tropics. Tropical forests are rich in species diversity, but little is known about the biology of many of the tropical forest tree species, and, in particular, information on the seed biology is very scanty. Until recently, indigenous trees were seldom used in forest replanting, preference being given to fast growing exotic species. A shortage of good quality indigenous forest tree seeds has contributed to this situation. However, studies on tropical forest tree seeds in general also remain more complex compared to those on annual crops, as a result of dormancy problems and large variations in seed longevity, compounding the handling problems. Acknowledging the important role that tree seeds play in the developing world, the International Plant Genetic Resources Institute (IPGRI) together with Danida Forest Seed Centre (DFSC) (now Forest & Landscape Denmark) initiated a project in 1995 to generate knowledge on the physiology of tropical tree seeds with particular emphasis on priority forest species. This book is the culmination of a six-year project, which aims to improve handling and storage of forest tree seeds. Participants from Africa, Asia and South/ Central America were trained, and gained sufficient experience during the execution of the project to ensure the creation of novel, detailed data sets to share with a global audience. A key feature of this project was its collaborative nature, such that investigations of most seed lots were replicated, usually in at least two countries, using the same standard protocols. These joint endeavours were communicated in the project newsletters, which reached many stakeholders worldwide. The end product is this book on the storability and management of seeds of 52 tropical forest tree species.It is noticeable that trends in the forestry sector are changing slowly, as more sustainable forest management is practised, and tree planting is becoming more diversified. A much larger number of economic, local tree species are increasingly being used, reflecting a change in emphasis from exotic species, such as from the genera Eucalyptus and Pin us, towards indigenous species. We have no doubt that this book is a contribution that will further boost the use of local tree species in forest planting programmes all over the tropics through proper handling of the seeds and promote tropical tree seed research and conservation.